Development and investigation of skin melanoma phantoms for ultrasonic examination - Andrėkutė, Kristina; Subotinaitė, Ilona; Valiukevičienė, Skaidra; Raišutis, Renaldas (Acta medica Lituanica, 2013)
Background. The purpose of this study was to develop skin mimicking phantoms with melanoma-like insertion with acoustic properties similar to the human skin. In order to guarantee that these phantoms are suitable for mimicking of the skin, we measured their parameters with an ultrasonography tool and compared with the human skin properties measured by other authors. Materials and methods. Distilled water, gelatin and Intralipid® 20% IV fat emulsion were mixed in different proportions thus manufacturing four models of the skin tissue. For melanoma-mimicking insertion only gelatin and distilled water were used. Ultrasonic examinations of manufactured phantoms were performed with the ultrasound system DUB-USB equipped with a mechanically scanned single-element focused transducer. Results. The speed of sound and the attenuation coefficient of all the manufactured phantoms were evaluated. This study demonstrates that the speed of sound decreases increasing concentration of Intralipid and it is close to the human skin tissue. The ultrasound velocity in the phantom material varied from 1 533.9 m/s up to 1 565.8 m/s depending on Intralipid fat emulsion concentration. The ultrasound velocity in the melanomalike insertion was 1  602.4  ±  23.5  m/s (mean  ±  SD). It was also found that the concentration dependent magnitude of attenuation increment matched the theoretically defined tendency. The attenuation in the range of 0.15–0.4  dB/mm/MHz was estimated in the phantoms possessing different concentrations of Intralipid. The attenuation in the melanomalike insertion region was 0.16  ±  0.02  dB/mm/MHz (mean  ±  SD). The magnitude of the attenuation coefficient is close to the attenuation in the human tissue. Conclusions. The four skin tissue mimicking phantoms were developed and their acoustic properties were estimated during this study. The investigation showed that the estimated speed of sound and the attenuation coefficient were close to the values being estimated in the human skin tissue. Furthermore, it was noted that the acoustic properties could be controlled by changing the concentration of Intralipid and such a flexible phantom could be used for mimicking of the external tissue of the human body.
Keywords: tissue mimicking phantom; ultrasonic properties; speed of sound; attenuation